The rate of eye comorbidities in patients with cataracts (results of a population study) - M.M. Bikbov; O.I. Orenburkina; T.R. Gilmanshin; A.E. Babushkin (РМЖ "Клиническая офтальмология")
M.M. Bikbov1, O.I. Orenburkina2, T.R. Gilmanshin1, A.E. Babushkin1 1Ufa Research Institute of Eye Diseases of the Bashkir State Medical University, Ufa, Russian Federation 2Russian Center for Eye and Plastic Surgery of Eye Diseases of the Bashkir State Medical University, Ufa, Russian Federation Aim: to assess the prevalence and characteristics of various types of cataracts and to analyze most common eye comorbidities from the population study "Ural Eye and Medical Study" (UEMS). Patients and Methods: this population study included 5899 individuals (3400 living in the rural area and 2499 living in the city). Eye examinations included uncorrected and best-corrected visual acuity measurements, autorefractometry, slit lamp examination, A-scan ultrasound biometry, non-contact tonometry, fundoscopic examination, corneal topography, fundus photography, static perimetry, and optical coherence tomography. Results: cataracts were diagnosed in 2616 patients (44.3%). These patients were more commonly rural residents and women. Nuclear cataracts (n=1575, 60.2%) were detected 1.5 times more often than cortical cataracts (n=1041, 39.8%). Eye comorbidities were diagnosed in 975 patients (37.3%). The most common eye comorbidities were retinal diseases. Among them, age-related macular degeneration (AMD) ranked first (13.46%). Glaucomatous optic neuropathy (GON)/glaucoma) and myopic macular degeneration/myopia were also common (6.77% and 4.93%, respectively). Diabetic retinopathy (DR) was reported less common (2.26%). The rate of eye comorbidities in patients was 43.6% in cortical cataracts and 33.1% in nuclear cataracts. As to individual conditions, the greatest difference was reported for AMD rate (19.12%) and macular hole/MH (1.8%), which were diagnosed twice more often in cortical cataracts (p<0.05) than in nuclear cataracts (9.71% and 0.8%, respectively). Conclusion: the structure of eye comorbidities in patients with nuclear and cortical cataracts was almost similar to that in patients with cataracts overall. However, the rate of eye comorbidities in patients with cortical cataracts was significantly higher than in patients with nuclear cataracts. This particularly applies to AMD and MH. In general, the rate of AMD, GON, DR, and MH in patients with complicated cataracts increases with age. These diseases were most often diagnosed in women and urban residents, except for AMD (more patients with AMD live in rural areas). Keywords: cataract, nuclear, cortical, eye comorbidities, population study. For citation: Bikbov M.M., Orenburkina O.I., Gilmanshin T.R., Babushkin A.E. The rate of eye comorbidities in patients with cataracts (results of a population study). Russian Journal of Clinical Ophthalmology. 2023;23(3):146–151 (in Russ.). DOI: 10.32364/2311-7729-2023-23-3-6.